Spatiotemporal characteristics and influencing factors of agricultural low-carbon economic efficiency in china - Ma, Dalai; Xiao, Yaping; Zhang, Fengtai; Zhao, Na; Xiao, Yuedong; Chuai, Xiaowei (Frontiers in Environmental Science, 2022)
Developing low-carbon agriculture can effectively avoid the waste of natural resources, thus contributing to agriculture's long-term sustainability. The Super-SBM model was used to evaluate the agricultural low-carbon economic efficiency of China's provinces from 2000 to 2018. And the temporal and spatial evolution characteristics were discussed. Simultaneously, a spatial panel data model with spatial effects is constructed based on the spatial economics principles, and the influencing factors of agricultural low-carbon economic efficiency are investigated. The results show that: (1) In terms of temporal evolution, the agricultural low-carbon economic efficiency in most provinces has declined over time, with only a few provinces improving. The agricultural low-carbon economic efficiency in China and three regions has changed consistently, exhibiting an obvious “L” trend, with a decline period and a stable period. (2) From the perspective of spatial differentiation, there are obvious differences in agricultural low-carbon economic efficiency across China's provinces. Provinces in the eastern region have higher agricultural low-carbon economic efficiency, while those in the central and western regions have lower agricultural low-carbon economic efficiency. In terms of specific provinces, Hainan's agricultural low-carbon economic efficiency has an absolute advantage, while Shanxi is the worst. (3) China's agricultural low-carbon economic efficiency shows obvious spatial agglomeration characteristics, particularly for H-H and L-L agglomeration, and this spatial agglomeration grows over time. The number of L-L agglomeration provinces increased over time, indicating that China's agricultural low-carbon economic efficiency has not improved significantly. (4) Economic growth level and Agricultural scientific and Technological progress have effectively improved agricultural low-carbon economic efficiency. However, Capital deepening, Government financial expenditure, Agricultural planting structure, and Agricultural disaster all have a negative impact, as does rural electricity consumption, but not significantly. To accelerate the development of low-carbon agriculture, all regions must not only pursue a differentiated low-carbon agriculture development path, but also to accelerate agricultural transformation, strengthen research and development, and popularize low-carbon agricultural technologies, reduce the input of traditional agricultural means of production, optimize the agricultural industrial structure, and adjust agricultural subsidy policies.